ACTIVITY OF ETHANOLIC EXTRACT FROM Justicia gendarussa Burm. LEAVES ON DECREASING THE URIC ACID PLASMA - Basah, Katrin; Elya, Berna; Amin, Juheini; Julian, Muhamad Iqbal (Makara Journal of Science, 2011)
The effect of Justicia gendarussa leaves extract has been investigated using oxonate-induced hyperuricemic male albino rats. In this experiment thirty five male albino rats were divided randomly into seven groups. There were three group doses variations of J. gendarussa extract that were 1.3 g/kg bw, 2.6 g/kg bw and 5.2 g/kg bw; two comparison groups that were allopurinol 0.68 g/kg bw and herbal “X” 0.85 g/kg bw; and two control groups that were induced control potassium oxonate 0.25 mg/kg bw and normal control CMC 0,5 %. Intraperitoneal administration of potassium oxonate 0.25 mg/kg bw was given one hour before administration of test drugs in eight day and plasma uric acid was measured in rats after two hours. Plasma uric acid was measured by spectrophotometric on 520 nm with enzymatic method. The results showed that all extracts could reduced uric acid level of rats. The decreasing potency of uric acid level was equal to doses increase, so the best result that can reduce uric acid level was J. gandarussa extract at a dose 5.2 g/ kg bw. This results indicated that J. gendarussa leaves extract may be effective for the prevention and the treatment of hyperuricemia.